Mobilising demand for primary health care services among urban slums: Insights from a case study in Bangladesh - Adams, Alayne M.; Rashid, Sabina F. (Taylor & Francis, 2022)
This article was published in Development in Practice by Taylor and Francis [Rights managed by Taylor & Francis 2021. ] and the definite version is available at: https://doi.org/10.1080/09614524.2020.1862763 The Journal's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2020.1862763